Анализ энергоэффективности беспроводных сенсорных сетей - Подпорин, Е. В.; Цопа, А. И. (ХНУРЕ, 2018)
Recent advances in semiconductor, networking and material science tech-nologies are driving the ubiquitous deployment of large-scale wireless sensor networks (WSNs).
Keywords: энергоэффективность; сенсорные сети; источник энергии